Urban Water Supply in Uttar Pradesh: A Case of Varanasi City - Singh, Arun K. (National Geographical Journal of India, 2022)
Water is an invaluable resource, essential for dignified human life and considered as human right. Water supply has drawn the attention of planners and policy makers since 1950s with a shift in focus from demand supply dynamics to reforms and restructure. But fact remains that a large section of urban population is not getting safe drinking water. Quality, quantity and service aspects are the issues of concerns. As per govt. records all the 623 urban centres (2001) of Uttar Pradesh are covered with piped water supply but only 31 percent of them have water supply as per demand of conservative 40 Ipcd norm. Within this backdrop the paper intends to examine the state and status of water supply in one of the metropolitan cities and the biggest urban centre of Eastern Uttar Pradesh i.e. Varanasi. The study restricted to the municipal water supply for domestic purpose and based on primary and secondary data sources. 12 Sample:wards are identified on the basis of purposive random sampling and 25 respondents with water supply system inside the house from each ward were identified. PRA and observation technique were used as supportive tools. Issues raised in the study are duration, timing and frequency of water supply, water storage device, its suitability for various household uses, quantity and quality aspect , finance involved in restoration of water supply system and improvement in the last few years. Finally a water supply governance matrix has been developed to show the state of water supply in the sample wards.